2013
DOI: 10.1108/13595471311315119
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health, neurodiversity and capacity to consent to sex

Abstract: Purpose -The purpose of this paper is to clarify: the law on capacity to consent to sex; ethical and legal factors in assessing decision-making capacity of those on the autism (ASD) and neurodiverse (ND) spectrums; and the legal obligations to promote sexual health devolving to local authorities from April 2013. We make proposals to ensure socio-sexual competence by providing appropriate sex and relationship education (SRE).Design/methodology/approach -Critical legal analysis of case law and legislation on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The concept area of sexual health centered primarily on information related to STDs (2.6/3), contraception (2.2/3), and reproductive health (2.1/3). It is important for curriculums to include the legal aspects that accompany engagement in sexual activity such as age of consent (Mackenzie & Watts, 2013). Alcohol and drugs should be addressed in sexual health as well as covered in other topical concept areas such as personal skills (decision making), given that the use of drugs and alcohol can lead to the impairment of decision making and engagement in risky behaviors (Blanchett & Wolfe, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The concept area of sexual health centered primarily on information related to STDs (2.6/3), contraception (2.2/3), and reproductive health (2.1/3). It is important for curriculums to include the legal aspects that accompany engagement in sexual activity such as age of consent (Mackenzie & Watts, 2013). Alcohol and drugs should be addressed in sexual health as well as covered in other topical concept areas such as personal skills (decision making), given that the use of drugs and alcohol can lead to the impairment of decision making and engagement in risky behaviors (Blanchett & Wolfe, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…4241/12, ECHR 20 May 2014. A solution more in keeping with local authorities' responsibilities for sexual health services would be to provide tailored SRE routinely for all those diagnosed as LD/ASD/ND (Mackenzie & Watts, 2013). This could be integrated with the revised SRE programmes which young people are currently demanding (Parker, 2014).…”
Section: Im V Lm: the Court Of Appeal Upholds A Low Threshold For Conmentioning
confidence: 96%
“…To ensure the sexual health, promote the right to sexual expression and redress inequalities pertaining to those diagnosed as having an autism spectrum disorder or otherwise neurodiverse [ASD/ND], and their families/carers, we advocated evidence-based SRE which addresses the individual differences and requirements of those with ASD/ND. We argued SRE incorporating family intervention [SREFIPs] should be developed to foster socio-sexual competence from childhood, to provide vulnerable children, young people, and adults with the requisite information and skills to exercise autonomy and avoid exploitation in their sexual decisions and practices (Mackenzie & Watts, 2013). To anchor these conclusions, we assessed recent English cases focused on the test for the capacity to consent to sex, and concluded that these revealed a regrettable confusion.…”
Section: The Capacity To Consent To Sexual Activity In Contextmentioning
confidence: 97%
See 1 more Smart Citation
“…Resolutions of specific clinical deficits are essential for people with HFA, and clinicians can use support groups to help persons with HFA learn how to make and keep friends [19,20]. The incorporation of these support groups by clinicians can even help these individuals meet romantic partners [21].…”
mentioning
confidence: 99%